Juges Sans Frontières? A Glocal Theory of Constitutional Interpretation - Rodrigo Camarena González (German Law Journal)
This article presents a “glocal” method of comparative constitutional interpretation. In the debate on the judicial use of foreign ideas, transnationalists claim to propose a simultaneously global and local approach. However, they perpetuate the methodological nationalism of globalists and localists by assuming nations as their primary units of analysis. In contrast, this article advances a truly glocal theory of judicial interpretation. The glocal is the product of a constant interplay between the global and the local, from the inception of an idea to its practical judicial application. This approach follows a three-step process. First, it provides a multiscale toolkit to demonstrate that ideas may have never been purely national in the first place but are the result of plural hybridizations. Second, it uncovers the units that generate and disseminate constitutional knowledge: trans-territorial networks united by thematically shared beliefs rather than by nationality or a global mission. Third, it equips judges with the ability to glocalize or customize the idea, not as an exercise of national differentiation but as a strategy to make it epistemically familiar and more politically appealing to the network. In this way, the article critically engages with the debate on constitutional transplants, challenging its nationalist bias.